Temporal and spatial distribution of harmful algal bloom (HAB) species in coastal waters of Kota Kinabalu, Sabah, Malaysia - Adam, Aimimuliani; Mohammad Noor, Normawaty; Anton, Ann; Saleh, Ejria; Saad, Shahbudin; Muhd Shaleh, Sitti Raehanah (Elsevier, 2011)
Development of harmful algal blooms (HABs) in coastal waters of Kota Kinabalu, Malaysia, is a recurring problem. The blooms are caused by Pyrodinium bahamense var. compressum and Cochlodinium polykrikoides. Recently, another potential HAB species, Gymnodinium catenatum, was identified. The occurrence of these species is known to be related to a range of factors, including seasonal monsoons, nutrients, physical parameters and geomorphology. To understand the occurrence and distribution of the three species, extensive samplings were carried out over a period of one year, including the South West Monsoon (SWM), North East Monsoon (NEM) and Inter-Monsoon (IM) periods, at 5 stations located in 3 different bays off Kota Kinabalu. Cell density of the three HAB species and in situ physical parameters (salinity, pH and temperature) were recorded. Secondary data such as rain fall and wind speed were obtained from the Meteorology Department, Kota Kinabalu. C. polykrikoides and G. catenatum occurred year-round with the highest cell densities of 1.54 107 cells L1 and 1.24 106 cells L1 in December (NEM). P. bahamense var. compressum was found in low numbers with maximum cell density of 2 104 cells L1 in August (SWM). The absence of P. bahamense var. compressum during the highest peak of C. polykrikoides and G. catenatum was related to nutrient concentrations and composition. The three species tended to occur at stations near the river and in a sheltered area. The results of the study indicate that the coastal area of Kota Kinabalu may continue to experience HAB problems, unless environmental conditions change significantly